TMIC-29. METABOLIC INTERACTIONS BETWEEN TREATMENT-RESISTANT SLOW-CYCLING CELLS AND THE IMMUNE SYSTEM IN HIGH-GRADE GLIOMA. (11th November 2019) - Sayour, Elias; Yang, Changlin; Tian, Guimei; Grippin, Adam; Dajac, Mariana; Nazareth, Brian; Andrews, Michael; Karachi, Aida; Mendez-Gomez, Hector; Stover, Brian; Moore, Ginger; Flores-Toro, Joseph; et al.
Abstract: INTRODUCTION: Intratumoral heterogeneity is increasingly recognized as a determinant of therapy resistance and disease recurrence; this is exemplified by glioblastoma (GBM), one of the most lethal malignancies. We recently revealed that GBM contain cell subpopulations with distinct metabolic requirements, with fast-cycling cells (FCCs) harnessing aerobic glycolysis, and treatment-resistant slow-cycling cells (SCCs) preferentially engaging lipid metabolism. How the different tumor cell populations interact with immune cells and how this metabolic heterogeneity shapes the immune landscape in GBM has yet to be understood. OBJECTIVES: The objectives of this study are to understand the mechanisms of communication in the tumor microenvironment, specifically to characterize the metabolic interactions between SCCs (a therapeutically resistant population of cancer cells that drive disease progression and recurrence) and the immune compartment. METHODS: The murine glioma cell line KR158 (derived from a Nf1;Trp53 mutant mouse) was used to establish the slow-cycling cell paradigm and metabolic heterogeneity in an immune-competent model of glioma. RESULTS: Similar to what we observed in patient-derived specimens, mouse KR158-derived SCCs demonstrate tumorigenicity, treatment resistance and up-regulation of stemness programs and lipid metabolic pathways. We determined that tumor progression is regulated by the interaction of SCCs with the immune system and established that these cells are driving a pro-tumorigenic microenvironment via the recruitment of immune suppressive myeloid cells. Importantly, the immune microenvironment shaped by SCCs is marked by specific metabolic features showing enhanced lipid exchange capacities that we propose are exploited by SCCs to support their survival and functions. CONCLUSION: Our study indicates that SCCs play a pivotal role in shifting the GBM milieu toward an immune regulatory phenotype but importantly reveals an unprecedented metabolic cooperation, which represents a novel therapeutic target to antagonize GBM.